Treatment of extrasphincter rectal fistulas with bioplastic substance application - A. M. Kuzminov; Sh. T. Minbayev; V. Yu. Korolik; L. P. Orlova; O. Yu. Fomenko; N. A. Polyakova; A. A. Safoyan; S. M. Khermez (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Cryptogenic, or common rectal fistulas are one of the most frequent disease in coloproctology. According to established classification, in relation to course of fistula in relation to sphincter muscle fibers, fistulas of rectum are classified to intrasphincteric, transsphincteric and extrasphincteric. The greatest difficulties arise at surgical treatment of extrasphincter fistulas of rectum that is related to high rate of relapse, and at application of ligature method, development of anal incontinence is impending. Today internal fistulous ostium plastic methods become more and more widespread, including those with application of bioplastic implants.Aim of investigation. To study potential of surgical treatment of extrasphincter fistulas of rectum by creation of inner fistula ostium by bioplastic substance «Collost».Material and methods. Experience of monitoring of 34 patients who underwent surgery for extrasphincteric fistulas of rectum of various degree of complexity with application of plastic material is presented.Results. At proctoplasty with application of bioplastic substance «Collost» no intraoperative complications developed, mean duration of surgical intervention was 45 minutes. Morbidity, including urine retention, edema of external hemorrhoids, were observed in 7 patients in postoperative period (20,6 %) and have been resolved conservatively. Complete convalescence was achieved in all patients, no relapses of fistula was observed during follow-up for 1 to 3 years.Conclusion. Surgical treatment of extrasphincter fistulas of rectum by formation of internal fistulous ostium by bioplastic substance «Collost» is pathogenicly proven. Its application allows to achieve permanent clinical effect, to decrease rate of postoperative morbidity, to reduce terms of rehabilitation of the operated patients.